2013
DOI: 10.1302/0301-620x.95b3.30344
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the serum level of C-reactive protein for the survival of patients with a primary sarcoma of bone

Abstract: The aim of this study was to determine whether the level of circulating C-reactive protein (CRP) before treatment predicted overall disease-specific survival and local tumour control in patients with a sarcoma of bone. We retrospectively reviewed 318 patients who presented with a primary sarcoma of bone between 2003 and 2010. Those who presented with metastases and/or local recurrence were excluded. Elevated CRP levels were seen in 84 patients before treatment; these patients had a poorer disease-specific surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 27 publications
8
52
1
1
Order By: Relevance
“…However, there are few studies performed to assess the association between CRP levels and prognosis of osteosarcoma patients. Nakamura et al assessed the prognostic value of the serum level of Creactive protein for the survival of patients with a primary sarcoma of bone [23]. A study published in 2011 showed that preoperative serum CRP was an independent prognostic factor for survival in patients with high-grade osteosarcoma, which was consistent with the findings in our study [24].…”
Section: Discussionsupporting
confidence: 90%
“…However, there are few studies performed to assess the association between CRP levels and prognosis of osteosarcoma patients. Nakamura et al assessed the prognostic value of the serum level of Creactive protein for the survival of patients with a primary sarcoma of bone [23]. A study published in 2011 showed that preoperative serum CRP was an independent prognostic factor for survival in patients with high-grade osteosarcoma, which was consistent with the findings in our study [24].…”
Section: Discussionsupporting
confidence: 90%
“…Of these, 11 were initially excluded after reading the abstracts (Figure 1). As a result, the systematic literature search generated a total of 2 datasets [5], [22] and 397 patients for ultimate analysis. These data were published from 2011 to 2013 to fit the inclusion criteria for our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The survival data were summarized from 2 eligible studies [5], [22] and analyzed the correlation between CRP and histological response to neoadjuvant chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations